A method for preparing a modified biological valve material
By calcining manganese dioxide and zinc oxide at high temperature into nanoparticles and combining with modifiers and anti-calcification agents, a modified biological valve material is formed, which solves the problem of easy calcification of biological valve materials, and significantly improves the anti-calcification performance and valve durability.
Patent Information
- Application Number
- CN202310554708.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-05-17
AI Technical Summary
Existing biological valve materials are prone to calcification during use, resulting in stiffness of the valve leaflets and limited mobility, reducing the durability of the biological valve.
A modified biological valve material is formed by grinding manganese dioxide and zinc oxide at high temperature and combined with a modifier and anti-calcification agent. This material increases hydrophilicity through nanoparticle adsorption, reduces platelet adhesion and aggregation, and combines anti-calcification agents to improve anti-calcification properties.
It significantly improves the anti-calcification performance of biological valves, extends the service life of the valve, avoids thrombosis, and improves the overall performance of the valve.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical technology, and in particular, relates to a method for preparing a modified biological valve material. Background Art
[0002] Heart valve disease is a cardiovascular disease with a high incidence caused by valve failure. Due to the special location of the heart valve, there is currently no effective treatment and heart valve replacement is often required. Artificial valve prostheses used for replacement surgery are divided into mechanical valves and bioprosthetic valves. Compared with mechanical valves, bioprosthetic valves have better hemodynamic properties and do not require lifelong anticoagulation.
[0003] Most of the bioprosthetic valve materials currently used in clinical practice are prepared using glutaraldehyde fixation technology. Glutaraldehyde itself is cytotoxic and is prone to calcification of valve leaflet tissue. Calcium and phosphate are deposited at specific sites to form calcium-phosphate crystals that gradually expand, making the valve leaflets stiff and limiting their mobility. Because of the calcification of bioprosthetic valves, structural valve failure occurs, leading to valve failure and reducing the durability of bioprosthetic valves.
[0004] In order to enhance the performance of biological valves, relevant technologies are currently available to modify the original biological valve materials to obtain biological valves with better performance. For example, the Chinese invention patent with application number CN202010470622.6 discloses an anti-calcification biological valve material and its preparation method. The method is: after the biological valve is immersed in an anti-calcification solution, it is placed in a glutaraldehyde solution to continue cross-linking; or the biological valve that has been cross-linked with glutaraldehyde is immersed in an anti-calcification solution; or the biological valve is immersed in an anti-calcification solution, and then placed in a glutaraldehyde solution for cross-linking, and finally immersed in an anti-calcification solution. For example, the Chinese invention patent with application number CN202110485836.5 discloses a preparation method of a modified biological valve material and a modified biological valve material, the method comprising: providing a modified biological valve material and terminal aldehyde-modified heparin, the modified biological valve material comprising a biological valve material and a hydrophilic polymer segment connected to the biological valve material, the end of the hydrophilic polymer segment having an amino group; subjecting the modified biological valve material to a reductive amination reaction with the terminal aldehyde-modified heparin to obtain a modified biological valve material.
[0005] The above-mentioned prior art obtains modified biological valve materials with anti-calcification or anticoagulation properties by modifying the original biological valve materials. However, such modified biological valve materials only have single anti-calcification or anticoagulation properties, which are still insufficient for the biological valve materials with excellent properties required in practice. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide a method for preparing a modified biological valve material. The method for preparing the biological valve material of the present invention is simple, the conditions are mild, and the obtained biological valve material has excellent performance.
[0007] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0008] One aspect of the present invention provides a method for preparing a modified bioprosthetic valve material, the method comprising the following steps:
[0009] Manganese dioxide and zinc oxide are mixed in a mass ratio of 1:0.5-1 and then calcined at high temperature, then ground into nanoparticles, the obtained nanoparticles are placed in toluene cyclohexanone and ultrasonically dispersed for 30 minutes, and then a modifier is added and heat treated at 60-80°C for 1-3 hours. After the reaction is completed, the solution is filtered through a membrane, and the obtained solution and an anti-calcification agent are stirred evenly to obtain a mixed solution;
[0010] The biological valve material is immersed in the above mixed solution for 24 hours, and then the biological valve material is taken out and washed with an inorganic solvent.
[0011] Preferably, the high temperature calcination conditions are: temperature 800-1000° C., time 2-4 h.
[0012] Preferably, the nanoparticles are added in an amount such that 1 g of the nanoparticles is dissolved in 2-4 ml of toluene cyclohexanone.
[0013] Preferably, the modifier is one or a combination of linear or star-shaped styrene-butadiene-styrene block copolymers.
[0014] Preferably, the anti-calcification agent is a micro-nano solution with anti-calcification function formed by compounds with different positive and negative charges in water, including positively charged substances and negatively charged substances in a mass ratio of 1:20-20:1; the positively charged substance is at least one of water-soluble chitosan, cationic polypeptides, gelatin, polylysine, polyarginine, polyhistidine, arginine, lysine, histidine, polyimide, and polyvinyl pyridinium salt; the negatively charged substance is at least one of a polyanion material and a negatively charged small molecule compound; the negatively charged substance is at least one of collagen, heparin, caprylic acid, capric acid, lauric acid, oleic acid, linoleic acid, arachidonic acid, linolenic acid, glutamic acid, aspartic acid, sodium dodecyl sulfate, sodium lauryl sulfate, polystyrene sulfonate, polyethylene sulfonate, and poly 2-acrylamido-2-methylpropane sulfonate.
[0015] Preferably, the mass ratio of the modifier to the anti-calcification agent is 1:1.
[0016] Preferably, the biological valve material comprises pericardium from cow, pig, horse, donkey and sheep.
[0017] Preferably, the inorganic solvent is water, physiological saline or pH neutral buffer.
[0018] By means of the above technical scheme, the present invention has at least the following advantages: the present invention firstly grinds the mixture obtained by high-temperature calcination of solid manganese dioxide and zinc oxide into nanoparticles, then disperses the obtained nanoparticles into toluene cyclohexanone, then adds a modifier for heat treatment, and the obtained solution is mixed with an anti-calcification agent for modifying the biological valve material, wherein the nanoparticles contained therein can be adsorbed on the biological valve, increase the hydrophilicity of the biological valve and reduce the adsorption performance of the biological valve material, and avoid the adhesion, aggregation and activation of platelets on the surface of the material to cause thrombosis. At the same time, the addition of an anti-calcification agent can increase the anti-calcification performance of the biological valve material.
[0019] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. Implementation
[0020] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0021] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0022] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:0.8 and calcined at 900°C for 3 hours, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles was dissolved in 3ml of toluene cyclohexanone) and ultrasonically dispersed for 30 minutes, and then star-shaped styrene-butadiene-styrene block copolymer was added and heat treated at 70°C for 2 hours. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the star-shaped styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including water-soluble chitosan and collagen in a mass ratio of 1:10. The porcine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed clean with an inorganic solvent.
[0023] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the bioprosthesis prepared in this embodiment has an anti-calcification effect that is more than 250 times higher than that of the traditional glutaraldehyde cross-linked valve. Example
[0024] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0025] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:0.5 and calcined at 900°C for 3 hours, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (adding 4 ml of toluene cyclohexanone per 1 g of nanoparticles) and ultrasonically dispersed for 30 minutes, and then star-shaped styrene-butadiene-styrene block copolymer was added and heat treated at 70°C for 2 hours. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the star-shaped styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including polyarginine and heparin in a mass ratio of 1:5. The porcine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed clean with an inorganic solvent.
[0026] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the bioprosthesis prepared in this embodiment has an anti-calcification effect that is more than 250 times higher than that of the traditional glutaraldehyde cross-linked valve. Example
[0027] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0028] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:1 and calcined at 900°C for 3 hours, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles was dissolved in 2ml of toluene cyclohexanone) and ultrasonically dispersed for 30 minutes, and then star-shaped styrene-butadiene-styrene block copolymer was added and heat treated at 70°C for 2 hours. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the star-shaped styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including linolenic acid and gelatin in a mass ratio of 1:5. The porcine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed clean with an inorganic solvent.
[0029] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the anti-calcification effect of the bioprosthesis prepared in this embodiment was improved by more than 220 times compared with the traditional glutaraldehyde cross-linked valve. Example
[0030] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0031] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:1 and calcined at 800°C for 4 hours, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles was dissolved in 3ml of toluene cyclohexanone) and ultrasonically dispersed for 30 minutes, and then star-shaped styrene-butadiene-styrene block copolymer was added and heat treated at 80°C for 1 hour. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the star-shaped styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including aspartic acid and polyimide in a mass ratio of 1:3. The porcine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed with an inorganic solvent.
[0032] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the anti-calcification effect of the bioprosthesis prepared in this embodiment was improved by more than 240 times compared with the traditional glutaraldehyde cross-linked valve. Example
[0033] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0034] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:0.5 and calcined at 1000°C for 2 hours, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles was dissolved in 4ml of toluene cyclohexanone) and ultrasonically dispersed for 30 minutes, and then linear styrene-butadiene-styrene block copolymer was added and heat treated at 60°C for 3 hours. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the linear styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including polylysine and caprylic acid in a mass ratio of 3:1. The bovine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed with an inorganic solvent.
[0035] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the anti-calcification effect of the bioprosthesis prepared in this embodiment was improved by more than 240 times compared with the traditional glutaraldehyde cross-linked valve. Example
[0036] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0037] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:0.5 and calcined at 900°C for 2h, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles was dissolved in 2ml of toluene cyclohexanone) and ultrasonically dispersed for 30min, and then linear styrene-butadiene-styrene block copolymer was added and heat treated at 60°C for 1h. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the linear styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including sodium dodecyl sulfate and water-soluble chitosan in a mass ratio of 1:5. The bovine pericardium membrane was soaked in the above mixed solution for 24h, and the biological valve material was taken out and then washed with an inorganic solvent.
[0038] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the anti-calcification effect of the bioprosthesis prepared in this embodiment was improved by more than 220 times compared with the traditional glutaraldehyde cross-linked valve. Example
[0039] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0040] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:0.6 and calcined at 1000°C for 3 hours, then ground into nanoparticles, the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles were dissolved in 3ml of toluene cyclohexanone) and ultrasonically dispersed for 30 minutes, and then linear styrene-butadiene-styrene block copolymer was added and heat treated at 70°C for 3 hours. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the linear styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including polyarginine and heparin in a mass ratio of 1:5. The bovine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed with an inorganic solvent.
[0041] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the anti-calcification effect of the bioprosthesis prepared in this embodiment was improved by more than 240 times compared with the traditional glutaraldehyde cross-linked valve. Example
[0042] A method for preparing a modified bioprosthetic valve material comprises the following steps:
[0043] Manganese dioxide and zinc oxide were mixed in a mass ratio of 1:0.9 and calcined at 800°C for 4 hours, then ground into nanoparticles, and the obtained nanoparticles were placed in toluene cyclohexanone (1g of nanoparticles was dissolved in 2ml of toluene cyclohexanone) and ultrasonically dispersed for 30 minutes, and then linear styrene-butadiene-styrene block copolymer was added and heat treated at 60°C for 3 hours. After the reaction was completed, the solution was filtered through a membrane, and the obtained solution and an anti-calcification agent (with a mass ratio of 1:1 to the linear styrene-butadiene-styrene block copolymer) were stirred evenly to obtain a mixed solution; the anti-calcification agent is a micro-nano solution with anti-calcification function formed in water by compounds with different positive and negative charges, including gelatin and oleic acid in a mass ratio of 1:3. The bovine pericardium was soaked in the above mixed solution for 24 hours, and the biological valve material was taken out and then washed with an inorganic solvent.
[0044] The tensile breaking stress of the bioprosthesis prepared in this embodiment under uniaxial tensile test (1*5cm sample size) is greater than 30N. The experiment of subcutaneous implantation in rats for 60 days found that the anti-calcification effect of the bioprosthesis prepared in this embodiment was improved by more than 220 times compared with the traditional glutaraldehyde cross-linked valve.
[0045] Test Example 1: Anticoagulant performance test of biological valve materials
[0046] The anticoagulant performance of the biological valve material of Example 1 and the traditional glutaraldehyde cross-linked valve (control example) was tested. The anticoagulant performance of the biological valve material was evaluated by the apoptosis time (APTT) test. The specific method was as follows: the modified biological valve material prepared in Example 1 and the traditional glutaraldehyde cross-linked valve material were placed in physiological saline at 37°C for 0, 1, 3, 7 and 15 days, and then the materials were immersed in platelet-poor plasma to detect the apoptosis time (APTT) of the plasma. The specific test results are shown in Table 1.
[0047] Table 1 Test results of anticoagulant performance of bioprosthetic valves
[0048]
[0049] It can be seen from the results in Table 1 that, compared with the control example, the biological valve material using the present invention has obvious anticoagulant activity; and after the modified biological valve material is immersed in physiological saline, the apoptosis time (APTT) is basically the same as that before immersion, indicating that the modified biological valve material of the present invention has stable anticoagulant activity.
[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified biological valve material, characterized in that: The method comprises the following steps Manganese dioxide and zinc oxide are mixed in a mass ratio of 1:0.5-1 and then calcined at high temperature, then ground into nanoparticles, the obtained nanoparticles are placed in toluene cyclohexanone and ultrasonically dispersed for 30 minutes, and then a modifier is added and heat treated at 60-80°C for 1-3 hours. After the reaction is completed, the solution is filtered through a membrane, and the obtained solution and an anti-calcification agent are stirred evenly to obtain a mixed solution; Soak the bioprosthetic valve material in the mixed solution for 24 hours, take out the bioprosthetic valve material and then wash it with an inorganic solvent; The modifier is one or a combination of linear or star-shaped styrene-butadiene-styrene block copolymers.
2. The method for preparing the modified bioprosthetic valve material according to claim 1, characterized in that: The high temperature calcination conditions are: temperature 800-1000°C, time 2-4h.
3. The method for preparing the modified biovalvular material according to claim 1, characterized in that: The nanoparticles are added in an amount such that 1 g of the nanoparticles is dissolved in 2-4 ml of toluene cyclohexanone.
4. The method for preparing the modified bioprosthetic valve material according to claim 1, characterized in that: The anti-calcification agent is a micro-nano solution with anti-calcification function formed by compounds with different positive and negative charges in water, including positively charged substances and negatively charged substances in a mass ratio of 1:20-20:1; the positively charged substance is at least one of water-soluble chitosan, cationic polypeptide, gelatin, polylysine, polyarginine, polyhistidine, arginine, lysine, histidine, polyimide, and polyvinyl pyridinium salt; the negatively charged substance is at least one of collagen, heparin, caprylic acid, capric acid, lauric acid, oleic acid, linoleic acid, arachidonic acid, linolenic acid, glutamic acid, aspartic acid, sodium dodecyl sulfate, sodium lauryl sulfate, polystyrene sulfonate, polyethylene sulfonate, and poly-2-acrylamido-2-methylpropane sulfonate.
5. The method for preparing the modified bioprosthetic valve material according to claim 1, characterized in that: The mass ratio of the modifier to the anti-calcification agent is 1:
1.
6. The method for preparing a modified bioprosthetic valve material according to claim 1, characterized in that: The biological valve materials include pericardium from cows, pigs, horses, donkeys and sheep.
7. The method for preparing a modified bioprosthetic valve material according to claim 1, characterized in that: The inorganic solvent is water, physiological saline or pH neutral buffer.
Citation Information
Patent Citations
Preparation method of modified bioprosthetic valve material and modified bioprosthetic valve material
CN115252901A
Anti-calcification biovalve material and preparation method thereof
CN111514375A
Valve material having long-acting antithrombosis property and preparation method therefor
WO2021254347A1